Financial acounting (Irwin/McGraw-Hill, 1997)
The Ninth Edition of Financial Accounting offers the first year accounting student an introduction to the preparation and use of financial accounting information. Accounting research and analysis has been significantly increased to provide a greater user-orientation, while coverage of procedures has been reduced. In addition, the Ninth Edition has two new co-authors, a new contemporary design, new pedagogical features including Internet activities, and a full support package.